Genome-Wide Identification of GRAS Gene Family in Daylily (Hemerocallis citrina Baroni) and Its Expression Profiles in Development, Hormone and Biotic Stress Response - Weijia Li; Hongying Sun; Zhiwen Chen; Yue Zhang; Jianguo Zhao (Biology, 2025)
The family of GRAS transcription factors plays an essential role in the regulation of plant development, the transmission of hormonal signals, and the adaptation to environmental stresses seen in numerous species. However, a comprehensive analysis of the GRAS family of Hemerocallis citrina (daylily) is lacking, despite its potential to help understand the stress content and developmental processes of the monospecies. This study identified 78 GRAS genes (HcGRAS) in H. citrina, which were classified into 15 subfamilies based on chromosomal location, gene structure, conserved motifs, and expression patterns. An analysis of promoter regions indicated a significant presence of elements related to hormones and stress, showcasing these genes’ role in adapting to environmental pressures. The GO and KEGG analyses indicated that HcGRAS genes were engaged in pathways associated with developmental processes and responses to environmental stress. Notably, HcGRAS38 was identified as a key interacting protein for SHR, SCR, and DELLA subfamily members, which suggested its central role in coordinating stress response and developmental signaling. Comparative genomic mapping with seven representative monocot and dicot species underscored evolutionary conservation and divergence in functions of the GRAS family. The expression profiling of 22 HcGRAS genes across different daylily tissues provided insights into their tissue-specific roles. This research may promote the further exploration of the functional characteristics of HcGRAS genes.